Endoscopic septotomy: an effective approach for internal drainage of sleeve gastrectomy-associated collections - Mahadev, Srihari; Kumbhari, Vivek; Campos, Josemberg M.; Galvao Neto, Manoel; Khashab, Mouen A.; Chavez, Yamile Haito; Bessler, Marc; Gonda, Tamas A. (Endoscopy, 2017)
Background and study aims Staple-line leaks occur in 1 % – 7 % of patients who undergo sleeve gastrectomy, and can be challenging to treat. The success of endoscopic approaches decreases as leaks develop into chronic sinus tracts. Endoscopic septotomy has been used to facilitate healing of refractory leaks by incision and enlargement of the tract to allow direct communication with the gastric lumen and internal drainage.Patients and methods We reviewed the technique and outcomes among patients who underwent endoscopic septotomy at two centers for the management of sleeve gastrectomy-associated gastric fistulas and perigastric collections refractory to occlusive endoscopic therapies. Results Nine patients underwent endoscopic septotomy at a mean of 8.6 weeks after leak diagnosis, following failure of percutaneous and conventional endoscopic modalities. Perigastric collections ranged from 3 cm to 10 cm in size. The mean procedure time for endoscopic septotomy was 87.2 minutes. Multiple endoscopic septotomy procedures (mean 2.3, range 1 – 4) were required to achieve radiological resolution. The mean follow-up period was 21.2 weeks, and all nine patients achieved symptom resolution without the need for surgery. Bleeding at the time of endoscopic septotomy occurred in three patients, and was managed with endoscopic clips and did not require transfusion. No other adverse events or delayed complications were recorded. Conclusions Endoscopic septotomy appears to be a safe and effective technique for the management of sleeve gastrectomy-associated fistulae and collections, including those refractory to other endoscopic and percutaneous methods.